Stritarjevi in Aškerčevi lirski popotni cikli - Žerjal-Pavlin, Vita (Slavistična revija, 2005)
In contrast to the prevailing narrative genres of travelogue literature, its lyrical genre is represented by the poems with travelogue motifs by Josip Stritar and Anton Aškerc, each of whom strung together three lyrical cycles of such poems. Since they sequenced them following the chronoptop of the travel, they compiled a non-dominant narrative structure of a syntagmatic cycle, i.e., implicitly a story of a travel and/or lyrical cyclic travelogue a variant of travelogue that was at the time very popular among Slovenes. However, with these cycles the two poets fulfilled different goals: Stirtar lyricized the basically narrative genre of travelogue, while Aškerc brought lyricism closer to the dominant narrative genres in Realism.
Keywords: Aškerc, Anton, 1856-1912; Aškerc, Anton: Iz popotnega dnevnika; lirika; potopisi; Slovene literature; slovenska književnost; Stritar, Josip, 1936-1923; Stritar, Josip: Popotne pesmi